Non-alcoholic fatty liver disease and risk of cardiovascular disease - Lonardo, Amedeo (2015)
Non-alcoholic fatty liver disease (NAFLD) has become the leading cause of chronic liver diseases worldwide, causing considerable liver-related mortality and morbidity. During the past decade, it has also become increasingly evident that NAFLD is a multisystem disease that affects many extra-hepatic organ systems, including the heart and the vascular system. In this updated clinical review, we discuss the rapidly expanding body of clinical and epidemiological evidence that supports a strong association of NAFLD with cardiovascular diseases (CVDs) and other functional and structural myocardial abnormalities. We also discuss some recently published data that correlate NAFLD due to specific genetic polymorphisms with the risk of CVDs. Finally, we briefly examine the assessment tools for estimating the global CVD risk in patients with NAFLD as well as the conventional and the more innovative pharmacological approaches for the treatment of CVD risk in this group of patients.